Intercultural Relations between Southern Iran and the Oxus Civilization. The Strange Case of Bifacial Seal NMI 1660. - Enrico Ascalone (Iranian Journal of Archaeological Studies, 2014)
New archaeological evidences of the so-called "Bactrian-Margiana Archaeological Complex" (= BMAC) has invited a change in our knowledge of the cultural relations between Oxus civilization and south-eastern Iran during the III-II millennium B.C. transition period. The new archaeological projects in southern and western Turkmenistan, as well as attested at Gonur Depe, have showed a wider and more articulated  relation in Asia Media, not only constrained to the movement of the Central Asian Bronze Age onto the Iranian plateau, Baluchistan, and western coast of the Persian Gulf. At the same time new research and excavations in the Jiroft valley has demonstrated a new cultural horizon in the eastern Iran. In this perspective the new information from the Oxus (Bactria and Margiana) and Jiroft civilizations invite new interpretations on III-II millennium historical relations among eastern areas. In particular it is possible to recognize south-eastern Iranian objects or influenced materials by Jiroft civilization in the Bactrian-Margiana archaeological complex. For these reasons the characteristic finds of BMAC recovered in Iran from Susa, Shahdad, Shahr-i Sokhta, Tepe Hissar, Khurab and Tepe Yahya have to be analyzed as part of a wider network and not simply explained with the movement of people from Central Asia towards southern Iran. An unpublished bifacial seal, now placed in the Bastan Museum, is an important line of evidence for a reassessment of the historical relations between two civilizations, representing a conceptual and ideological creation originated by the union of southern Iran and Central Asian cultural developments. This evidence is a new and decisive contribution for the understanding of the intercultural processes between the Oxus and Jiroft cultures; its presence confirms a homogeneous and related-artistic knowledge in a wide territory from Margiana and Bactria to the Lut, Jiroft, and Elam regions in a joint cultural source, but with different indigenous developments.